The Impact of Gig Economy Growth and Islamic Bank Financing on Youth Unemployment Rates in Indonesia - Ade Fahdiya Syakhilah; Marliyah; Nursantri Yanti (MALIA: Jurnal Ekonomi Islam, 2026)
Introduction: High youth unemployment in Indonesia reflects a mismatch between labor force growth and the availability of formal employment. At the same time, the expansion of the digital platform–based gig economy offers flexible job opportunities for young people, while Islamic bank financing holds potential to stimulate productive economic activities through profit-sharing schemes. However, empirical evidence on the effectiveness of these sectors in reducing youth unemployment remains limited. This study examines the impact of gig economy growth and Islamic bank financing on youth unemployment in Indonesia.Methods: A quantitative approach was applied using panel data from 34 provinces during 2019–2023. Panel regression analysis was employed, with model selection through Chow and Hausman tests, which identified the Fixed Effect Model as the most appropriate. Robust Standard Errors were used to correct heteroscedasticity.Results: Gig economy growth shows a negative and significant effect on youth unemployment, indicating its role in absorbing young workers. In contrast, Islamic bank financing has a positive and significant effect, suggesting that financing has not been optimally directed toward labor-intensive sectors or young productive entrepreneurs. Jointly, both variables significantly influence youth unemployment, with an explanatory power of 87.4%.Conclusion and Suggestion: The gig economy functions as an effective short-term employment channel, whereas Islamic financing requires policy reorientation toward youth-driven productive sectors. It is also necessary to enhance Islamic financial literacy and strengthen integration with the digital gig ecosystem to maximize its impact on reducing youth unemployment.Practical Implications: The findings provide important insights for policymakers, financial institutions, and digital platform providers in designing strategies to reduce youth unemployment. Strengthening collaboration between Islamic banks and gig platforms, improving access to financing for young entrepreneurs, and promoting inclusive digital ecosystems can enhance employment opportunities and economic participation among youth.Originality/Value: This study contributes to the literature by integrating the roles of the gig economy and Islamic bank financing in a single empirical model using panel data across Indonesian provinces. It offers a novel perspective on how digital labor markets and Sharia-compliant financial systems jointly influence youth employment in a developing country context.